KEDUDUKAN KAPAL PERANG YANG MASUK KE DALAM WILAYAH ZEE INDONESIA - Dicky Elvando; Muh. Jufri Ahmad (Gapenas Publisher, 2023)
Regulation is a basis for the utilization of marine resources, therefore the Government of Indonesia has implemented its Constitution as a law and basic rules. These regulations need further elaboration. Therefore, the Government of Indonesia stipulates laws and regulations relating to the utilization of fishery resources and sea boundaries in Law number 17 of 1985 of the ratification of UNCLOS 82, and in practice these laws and regulations may not deviate from the Constitution. Republic of Indonesia. The abundance of marine fishery resources in Indonesia's Exclusive Economic Zone allows for actions that are detrimental to Indonesia as a coastal country due to violations committed by neighboring countries that violate state sovereignty. This research will rely on normative juridical research by relying on laws and regulations and other documents, both primary and secondary. Apart from being alert to violations from neighboring countries that can commit illegal fishing, exploitation of natural resources, and illegal conservation in order to gain unilateral benefits that will threaten the country's sovereignty, it is also unavoidable that foreign military ships passing by often guard and cross the territorial zone. blatantly exclusive economy. Of course this is a warning to the state in maintaining its sovereignty so that it is protected from foreign intervention which could secretly steal data on the territory of a coastal state and look for loopholes in defense weaknesses through maritime boundaries. With that the law of the sea which regulates the boundaries of the exclusive economic zone and has been summarized in UNCLOS 82, has become Indonesia's reference for determining the position of a warship entering and crossing the exclusive economic zone